Plug in x = 0 and it leads to y = 0. This is because
y = (1/2)*x
y = (1/2)*0 ... x has been replaced with 0
y = 0
So the point (0,0) is on the graph of the equation.
Now plug in x = 2 and follow the same steps as above
y = (1/2)*x
y = (1/2)*2 ... replace x with 2
y = 1
So x = 2 leads to y = 1 giving us the point (2,1)
Plot the points (0,0) and (2,1). Then draw a straight line through these two points to draw the graph of the equation.
See attached for a visual.
Side Note: 1/2 = 0.5 so y = (1/2)x is the same as y = 0.5x